Clonal and resistance profiles of fluoroquinolone-resistant uropathogenic Escherichia coli in countries with different practices of antibiotic prescription - Choudhury, Debarati; Alanbari, Rawan; Saveliev, Pauline; Sokurenko, Evgeni; Fuzi, Miklos; Tchesnokova, Veronika (Frontiers in Microbiology, 2024)
Background Antibiotic prescription practices differ between countries, influencing regional antimicrobial resistance prevalence. However, comparisons of clonal diversity among resistant bacteria in countries with different prescribing practices are rare. The rise of fluoroquinolone-resistant Escherichia coli (FQREC), often multidrug-resistant, exacerbates global antibiotic resistance. Unlike in the USA, antibiotics are commonly dispensed in Iraq without prescriptions, leading to widespread overuse and misuse. This study aimed to assess the impact of varying antibiotic use practices on FQREC diversity. Methods We compared FQREC prevalence, multidrug resistance, and clonality of FQREC among E. coli isolated from urine submitted between 2017 and 2018 to three US hospitals and two Iraqi hospitals. All FQREC isolates were analyzed for QRDR mutations and the presence of PMQR genes. A subset of FQREC strains from the ST131-H30R/Rx subgroups underwent whole-genome sequencing (WGS) and phylogenetic analysis. Results E. coli from Iraq showed significantly higher resistance to all tested antibiotics compared to those from the USA, with 76.2% being FQREC versus 31.2% in the USA (p < 0.01). Iraqi FQREC strains were more frequently multidrug resistant. The predominant subgroup in both countries was ST131-H30, with the notable absence of ST1193 among Iraqi FQREC. Iraqi-origin ST131-H30 strains exhibited higher minimum inhibitory concentrations (MICs) for ciprofloxacin and greater resistance to third-generation cephalosporins (3GC), trimethoprim/sulfamethoxazole (TMP/STX), and imipenem (IMI) than those from the USA. Increased 3GC resistance in Iraqi strains was linked to a higher proportion of blaCTX-M-15-carrying H30Rx subclade isolates. Additionally, Iraqi H30 strains exhibited higher MICs for fluoroquinolones due to more frequent carriage of PMQR determinants compared to US strains. Whole-genome sequencing was performed on 46 Iraqi and 63 US H30 isolates. Phylogenetic analysis revealed two clades—H30R and H30Rx—present in both countries, with isolates from both regions distributed throughout, without the emergence of distinct new major subclones. However, Iraqi isolates tended to cluster in separate subclades, indicating endemic circulation of the strain groups. Conclusion In regions like Iraq, where antibiotics are overused and misused, resistance among uropathogenic E. coli to various antibiotics is significantly higher. Most Iraqi resistant strains belong to well-known international groups, and no new highly successful strains have emerged. The absence of ST1193 in Iraq may reflect regional, socioeconomic, demographic, or cultural factors that hinder the success of certain strain groups in the country.